2018
DOI: 10.1111/tmi.13133
|View full text |Cite
|
Sign up to set email alerts
|

Risk of active tuberculosis among people with diabetes mellitus: systematic review and meta‐analysis

Abstract: There is evidence suggesting an increased risk of developing TB among people with DM, and that improving glycaemic control in DM patients would reduce the risk of developing TB. An integrated approach is needed to control the dual burden of DM and TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 37 publications
(70 reference statements)
0
54
0
1
Order By: Relevance
“…This study demonstrated that most TB patients had already suffered from diabetes. This discovery is according to a research by Hayashi and Chandramohan who conducted a meta-analysis of 14 studies [11]. Most respondents had a period of 0-5 years from being diagnosed with DM to being diagnosed with TB and are new TB patients.…”
Section: Discussionmentioning
confidence: 98%
“…This study demonstrated that most TB patients had already suffered from diabetes. This discovery is according to a research by Hayashi and Chandramohan who conducted a meta-analysis of 14 studies [11]. Most respondents had a period of 0-5 years from being diagnosed with DM to being diagnosed with TB and are new TB patients.…”
Section: Discussionmentioning
confidence: 98%
“…In acutely unwell patients, under-nutrition may also increase the risk of inpatient death due to increased risk of severe metabolic and electrolyte disturbances [1618]. Type 2 Diabetes Mellitus (T2DM) is another known risk factor for active TB [19]. T2DM, especially when poorly controlled, may increase the risk of death and relapse during TB disease [20] whilst TB may also negatively affect glycaemic control [21].…”
Section: Introductionmentioning
confidence: 99%
“…The complexity of the disease is due to many factors including the ability of Mycobacterium tuberculosis (Mtb), the causative agent of TB, to enter slow/non-replicating states, to remodel metabolic and respiratory systems, to cause latent infection, together with the increasing emergence of drug-resistant Mtb (Ayabina et al, 2016;Dheda et al, 2017;Bekele et al, 2018;Gordon and Parish, 2018;Singh et al, 2019). The impact of TB is also worsened by the high rate of Mtb infections among patients with chronic diseases like diabetes mellitus and HIV infection (Hayashi and Chandramohan, 2018;Fernandez et al, 2020). Among people living with HIV, the progression from TB infection to disease occurs at a high rate, positioning TB as the leading cause of mortality in this population (Peters et al, 2019).…”
Section: Introductionmentioning
confidence: 99%